FEASIBILITY STUDY USING ACTIVATED THE REAGENT SOLUTION FOR PURIFICATION OF WASTE WATER FROM A PHOSPHORUS COMPOUND (Municipal economy of cities. Series: «Economy science», 2013)
The article shows the economic feasibility of post-treatment technology of waste water from phosphorus compounds on the basic of pilot tests.